Hydrogen selective filters based on nanostructured substrates and multilayer nanosize NbTi and TiNi layers - Ryabchikov A. I. Aleksandr Ilyich; Golovkov V. M.; Stepanov I. B. Igor Borisovich; Sohoreva V. V.; Shulepov I. A. Ivan Anisimovich (2010, 2010)
The results of investigations of the membrane-selective properties of the nanosize multilayer structures on the basis of the composition of niobium, titanium and nickel as the most perspective candidates for the creation of the hydrogen membranes with improved characteristics are presented in the paper. Such membrane represents the system of nanosize TiNb, NiTi layers deposited on the substrates of porous stainless steel and columnar nanostructure of Ni. The substrates with columnar structures were formed by means of electrolytic deposition of nickel through the template from the nuclear track membrane. With the help of the plasma deposition of alternating layers of NbTi and Ti or TiNi with the layer thickness from units of nanometers to several tens of nanometers there were formed the structure-gradient coatings, preventing the emergence of hydrogen embrittlement, and at the same time preserving high selectivity and permeability. NbNi and TiNi layers were formed using the vacuum-arc discharge plasma filtered from microparticle fraction. The investigation of selective properties of the formed membranes was performed on a specially developed model of the hydrogen filter. As a result of investigations of the filtering device parameters, there was obtained the following: selectivity by hydrogen made 99.99% at the efficiency up to 10 m3/(h ⋅ m2)